Synthesis and photo-induced anticancer activity of new 2-phenylethenyl-1H-benzo[e]indole dyes - Varvuolytė, Gabrielė; Řezníčková, Eva; Krikštolė, Sonata; Tamulienė, Rasa; Bieliauskas, Aurimas; Malina, Lukáš; Vojáčková, Veronika; Duben, Zdenko; Kolářová, Hana; Kleizienė, Neringa; Arbačiauskienė, Eglė; Žukauskaitė, Asta; et al. (European journal of medicinal chemistry, 2024)
Herein, a series of new 1,1,2-trimethyl-1H-benzo[e]indole dyes was prepared via Knoevenagel condensation reaction between 1,1,2-trimethyl-1H-benzo[e]indole and benzaldehydes, and characterized using various spectroscopic methods. The obtained compounds showed cytotoxic properties in G361 melanoma cell line upon irradiation with 414 nm blue light at submicromolar doses. The mechanism of action of the most potent compound 15 was further investigated. The treatment induced substantial generation of reactive oxygen species, leading to DNA damage followed by cell death depending on the concentration of the photosensitizer compound and the irradiation intensity.
Keywords: Dose-Response Relationship, Drug; DNA Damage; photo-induced activity; Structure-Activity Relationship; Photosensitizing Agents; reactive oxygen species; nádorové buněčné linie; barvicí látky; fotosenzibilizující látky; screeningové testy protinádorových léčiv; Molecular Structure; protinádorové látky; reaktivní formy kyslíku; Indoles; Antineoplastic Agents; Coloring Agents; Reactive Oxygen Species; molekulární struktura; Knoevenagel condensation; benzo[e]indole; poškození DNA; DNA damage; Cell Line, Tumor; vztahy mezi strukturou a aktivitou; Light; indoly; lidé; proliferace buněk; Humans; světlo; Drug Screening Assays, Antitumor; vztah mezi dávkou a účinkem léčiva; Cell Proliferation